Differences in subthalamic oscillatory activity in the two hemispheres associated with severity of Parkinson’s disease - Zhao, Xuemin; Zhuang, Ping; Hallett, Mark; Zhang, Yuqing; Li, Jianyu; Wen, Yi; Li, Jiping; Wang, Yunpeng; Hu, Yongsheng; Li, Yongjie (Frontiers in Aging Neuroscience, 2023)
Background: It is well known that motor features of Parkinson’s disease (PD) commonly begin on one side of the body and extend to the other side with disease progression. The onset side generally remains more severely affected over the course of the disease. However, the pathophysiology underlying the asymmetry of motor manifestations remains unclear. The purpose of the present study is to examine whether alterations in neuronal activity in the subthalamic nucleus (STN) associate with PD severity. Methods: Microelectrode recording was performed in the STN during targeting for 30 patients in the treatment of deep brain stimulation. The mean spontaneous firing rate (MSFR), power density spectral analysis, and correlations were calculated. Characteristics of subthalamic oscillatory activity were compared between two hemispheres. UPDRS III scores during “Off” and “On” states were obtained for the body side of initial symptoms (BSIS) and the body side of extended symptoms (BSES). Results: There were significant differences of MSFR (41.3 ± 11.0 Hz vs 35.2 ± 10.0 Hz,) and percentage of ß frequency oscillatory neurons (51.3% vs 34.9%) between BSIS and BSES. The percentage of ß frequency oscillatory neurons correlated with the bradykinesia/rigidity scores for both sides (p <0.05). In contrast, the percentage of tremor frequency oscillatory neurons was significantly higher in the BSES than that in the BSIS. In particular, these neurons only correlated with the tremor scores of the BSES (p <0.05). Conclusion: The results suggest that increased neuronal firing rate and ß frequency oscillatory neurons in the STN are associated with severity of PD and its progression. Tremor frequency oscillatory neurons are less observed in the STN of the BSIS suggesting that ß oscillatory activity dominates and tremor frequency oscillatory activity reciprocally declines.